Development of an organ procurement team in South Australia in response to COVID‐19. Issue 7 (23rd May 2022) - Gimpel, Damian Joseph; Crouch, Gareth; Szpytma, Malgorzata; Mazzone, Annette; Baker, Robert A.; Bennetts, Jayme S.
Abstract: Background: Due to the nature of border closures and quarantine requirements in Australia during the COVID‐19 pandemic, the feasibility of interstate travel for organ retrieval created complex logistics. An organ procurement service in South Australia, to procure heart and lungs of local donors, was commenced to mitigate the impact of the travel restrictions imposed due to COVID‐19. The purpose of this review was to examine the initial data and feasibility of the service. Methods: A single unit, multi‐site retrospective review from April 2020–August 2021 of all organ retrievals undertaken by the Flinders Medical Centre cardiothoracic service across Adelaide metropolitan area. Data was prospectively collected and analysed from the DonateLife South Australian centralized database. All data was de identified. Results: A total of 25 organ procurements had been undertaken across 17 months since commencing the program. Total of 9 hearts and 16 bilateral lungs were procured with median age of donor of hearts 49 years (IQR 35.5–51. 5) and 60 years (IQR 44–72) for lung donation. Six organs were donated after determination of circulatory death and 19 after neurological determination of death. Median ischaemic time for heart donation was 4.4 h (IQR 3.0–5.8) and lung donation 4.4 h (IQR 3.4–6.1). All organs procured by the local South Australian team were successfully transplanted at the recipient site. Recipient sites included 8 in Victoria, 10 in New South Wales, 4 in Western Australia and 3 in Queensland. Conclusions: The necessity of flexibility within the field of cardiothoracic surgery is evident during the COVID‐19 pandemic. The implementation of an organ retrieval service in South Australia has been successful with no apparent increased risk to successful transplant outcomes. Abstract : This manuscript describes the experience of commencing an organ retrieval service in South Australia during COVD‐19. There was previously no local organ cardiothoracic retrieval service in South Australia which was problematic with border closures in Australia. The develop of local organ procurement teams and the relationship between interstate tertiary hospitals clearly demonstrates the fantastic collaboration between the cardiothoracic surgical community for ultimately the benefit of the patient and decreased risk to staff and cardiothoracic transplant units.